The Influence of the Oil and Gas Industry on Socioeconomic Inequality in the Bojonegoro Market: A Sharia Economic Perspective - Vica Aurelia Hartantri; Abdur Rohman (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2026)
This study aims to analyze the influence of the oil and gas industry on socio-economic inequality in the market aspect of Bojonegoro Regency from the perspective of Islamic economics. Using a descriptive quantitative approach, the research was conducted in areas surrounding oil and gas exploitation sites, employing data collection methods such as observation, semi-structured interviews, and documentation studies. The results indicate that the oil and gas industry has transformed the local market structure into an oligopolistic system, where large-capital business actors dominate the trade and service sectors, leading to economic exclusion of micro and small enterprises. Additionally, the surge in goods and service prices has increased the cost of living without being balanced by equitable income distribution among the local community. A simple linear regression analysis shows a significant but weak relationship between the presence of the oil and gas industry and the increase in local community income (R² = 0.28). From the perspective of Islamic economics, this condition contradicts the principles of distributive justice (al- ‘adl) and public welfare (maslahah). Therefore, affirmative policies from local governments and more equitable and sustainable corporate social responsibility programs by oil and gas companies are needed to realize socio-economic balance in oil and gas-producing regions.